Challenges and Perspectives for Immunotherapy in Adenocarcinoma of the Pancreas: The Cancer Immunity Cycle. Issue 2 (February 2018) - Kieler, Markus; Unseld, Matthias; Bianconi, Daniela; Prager, Gerald
Abstract : Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a lethal disease with a devastating 5-year overall survival of only approximately 7%. Although just 4% of all malignant diseases are accounted to PDAC, it will become the second leading cause of cancer-related deaths before 2030. Immunotherapy has proven to be a promising therapeutic option in various malignancies such as melanoma, non–small cell lung cancer (NSCLC), microsatellite instability-high gastrointestinal cancer, urinary tract cancer, kidney cancer, and others. In this review, we summarize recent findings about immunological aspects of PDAC with the focus on the proposed model of the "cancer immunity cycle". By this model, a deeper understanding of the underlying mechanism in achieving a T-cell response against cancer cells is provided. There is currently great interest in the field around designing novel immunotherapy combination studies for PDAC based on a sound understanding of the underlying immunobiology.